Embedded systems architecture a comprehensive guide for engineers and programmers - Noergaard, Tammy (Elsevier/Newnes, 2013)
Suitable for those starting out as technical professionals such as engineers, programmers and designers of embedded systems; and also for students of computer science, computer engineering and electrical engineering, this book offers a guide to understanding the components that make up an embedded system's architecture.